Obsolete Laws: Economic and Moral Aspects, Case Study-Composting Standards. - Vochozka, Marek; Maroušková, Anna; Šuleř, Petr (Science & Engineering Ethics, 2017)
From the early days of philosophy, ethics and justice, there is wide consensus that the constancy of the laws establishes the legal system. On the other hand, the rate at which we accumulate knowledge is gaining speed like never before. Due to the recently increased attention of academics to climate change and other environmental issues, a lot of new knowledge has been obtained about carbon management, its role in nature and mechanisms regarding the formation and degradation of organic matter. A multidisciplinary techno-economic assessment of current composting standards and laws that took into account the current state of knowledge about carbon management was carried out as a case study. Economic and environmental damage caused by outdated laws was revealed. In addition, it was found that the introduction of the best composts into the market is permitted, causing additional negative environmental as well as economic impacts.